2019
DOI: 10.1177/1475921719876045
|View full text |Cite
|
Sign up to set email alerts
|

A structural health monitoring system for data analysis of segment joint opening in an underwater shield tunnel

Abstract: The opening of segment joints is considered critical for the stability analysis of a shield tunnel lining. In order to prevent tunnel disasters, an integrated framework was developed in this study based on the laboratory experiment, real-time monitoring, and statistic theory. As a case study, this presented method was employed in a typical underwater shield tunnel to prevent leakage disasters. The water pressure experiment was used to analyze the importance of joint openings for the tunnel waterproofing. Then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…There have been plenty of studies on the reliable techniques used to test the actual status of tunnels in the field. Furthermore, numerical simulation is a common method used to analyze the mechanical response of structures under various boundary conditions [7,9]. Numerical simulation in light of field investigation data is vitally important for preventing disasters [18], which remains a challenge.…”
Section: Framework For Local Damage Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been plenty of studies on the reliable techniques used to test the actual status of tunnels in the field. Furthermore, numerical simulation is a common method used to analyze the mechanical response of structures under various boundary conditions [7,9]. Numerical simulation in light of field investigation data is vitally important for preventing disasters [18], which remains a challenge.…”
Section: Framework For Local Damage Assessmentmentioning
confidence: 99%
“…Numerical simulation in light of field investigation is vitally important for disaster prevention. It is of great significance to combine field investigation with mechanical response analysis [2,3,7]. Based on the current research, this work developed an integrated framework to detect the damage conditions of the concrete structure and analyze the influence of local damage on structural mechanical performance through nondestructive testing (NDT) technology and numerical models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of structural mechanical behaviors is vitally important for maintaining its stability, especially for underground constructions because the geological conditions and field environment of underground engineering are complex. The existing researches (Tan et al, 2019; Yang et al, 2018) indicated that water pressure, soil pressure and temperature are the main loads to influence the stability of structure. In traditional studies, temperature is considered as evenly distributing in tunnel, which is not agree with the actual conditions (Jun et al, 2017; Oluwaseun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The temperature variation is one of the most important factors to influence the mechanical behaviors of concrete structure (Tan et al, 2019; Yang et al, 2018). In order to analyze the impact of temperature which imposed on concrete structure, an integrated method is performed in this study.…”
Section: Introductionmentioning
confidence: 99%